Features of the formation of an effective mechanism of public administration of health care institutions in the context of medical care for military personnel - N. V. Humenna; N. M. Kalyniuk (Науковий вісник Ужгородського національного університету. Серія Право)
The article investigates and analyses the peculiarities of forming an effective mechanism of public administration of health care institutions in the context of medical care for military personnel. It is found that ensuring the exercise of the right to health for every Ukrainian during martial law in equal proportions is a rather difficult task, but the availability of basic medical services, even if these services cannot be provided in full everywhere, is a rather good indicator for a country which has been at war for a long time. It is substantiated that the mechanism of public administration of healthcare facilities providing medical care to military personnel should be aimed at observing human rights in the field of healthcare under martial law to ensure the protection of public health, prevent suffering and minimise the consequences of the conflict. The author establishes that the key to ensuring the exercise of the military personnel’s rights to health care and medical assistance is their awareness of these rights and the mechanisms for their exercise. The author analyses the legal provisions relating to the military’s rights to healthcare. It is proved that it is necessary to preserve the benefits for war veterans, but it is also important to refine and improve the mechanisms for their implementation. It is necessary to develop effective mechanisms to ensure the efficient use of available resources, improve the system of monitoring and control over the implementation of benefits, and take into account the individual needs of veterans in the development and implementation of social programmes. It is concluded that the real implementation of the social rights and freedoms of servicemen and women contributes to maintaining and enhancing their combat readiness and combat capability. The feeling of support and security is important for servicemen, as it can have a positive impact on their psychological state and combat capability. When military personnel know that their health care needs and rights will be addressed and protected, they can be more relaxed and focus on their duties in combat. This is important for maintaining their combat readiness and mission effectiveness. Thus, providing support and protection to military personnel can have a direct impact on the success of their service. But, unfortunately, in practice, the military are not always able to fully exercise their rights.